PENGENALAN SOFTWARE DAN HARDWARE KOMPUTER GUNA MENINGKATKAN WAWASAN TEKNOLOGI KEPADA SISWA - Agus, Raja Tama Andri; Sibuea, Mustika Fitri Larasati; Julita, Rina; Ramadhani, Andrew; Sembiring, Muhammad Ardiansyah (Smart Education, 2025)
Abstract: In the increasingly developing digital era, understanding technology is an important aspect in the world of education, especially for students who will face the challenges of the industrial era 4.0. Currently, there is still a gap in students' understanding of computer hardware and software, which has the potential to hinder their readiness to adopt and utilize technology optimally. Therefore, increasing technological insight from an early age is very necessary so that students do not only become passive users of technology, but also understand the working principles of computers and their potential in various fields. Introduction to computer hardware includes an understanding of the main components such as processors, memory (RAM), hard drives, motherboards, and input and output devices. Meanwhile, understanding of software includes operating systems, productivity applications, and learning support software. To improve the effectiveness of learning, interactive methods are needed such as live demonstrations, the use of digital learning media, and computer laboratory practices. With a combination of theory and practice, students can understand how computers work and how to use them effectively. The urgency of this community service lies in the need to improve students' technological insight so that they have adequate digital skills to face the increasingly rapid development of technology. Therefore, the results of this community service will be published in a SINTA 5 accredited journal and disseminated through mass media, such as technology-based journals. aims to expand the impact of community service, so that it can provide broader benefits to the world of education and society. Thus, this community service is expected to be a reference in the development of technology-based learning methods and help improve students' technological insight so that they are better prepared to face digital challenges in the future. Keywords: Computer Hardware; Computer Software; Technology Insight; Students Abstrak: Di era digital yang semakin berkembang, pemahaman teknologi menjadi aspek penting dalam dunia pendidikan, khususnya bagi siswa yang akan menghadapi tantangan era industri 4.0. Saat ini, masih terdapat kesenjangan dalam pemahaman siswa mengenai perangkat keras (hardware) dan perangkat lunak (software) komputer, yang berpotensi menghambat kesiapan mereka dalam mengadopsi serta memanfaatkan teknologi secara optimal. Oleh karena itu, peningkatan wawasan teknologi sejak dini sangat diperlukan agar siswa tidak hanya menjadi pengguna teknologi yang pasif, tetapi juga memahami prinsip kerja komputer serta potensinya dalam berbagai bidang.Pengenalan hardware komputer mencakup pemahaman tentang komponen utama seperti prosesor, memori (RAM), hard drive, motherboard, serta perangkat input dan output. Sementara itu, pemahaman tentang software meliputi sistem operasi, aplikasi produktivitas, serta perangkat lunak pendukung pembelajaran. Untuk meningkatkan efektivitas pembelajaran, diperlukan metode interaktif seperti demonstrasi langsung, penggunaan media pembelajaran digital, serta praktik laboratorium komputer. Dengan kombinasi teori dan praktik, siswa dapat memahami bagaimana komputer bekerja dan bagaimana menggunakannya secara efektif. Urgensi pengabdian ini terletak pada kebutuhan peningkatan wawasan teknologi bagi siswa agar mereka memiliki keterampilan digital yang memadai untuk menghadapi perkembangan teknologi yang semakin pesat. Oleh karena itu, hasil pengabdian ini akan dipublikasikan dalam jurnal terakreditasi SINTA 5 serta disebarluaskan melalui media massa, seperti jurnal berbasis teknologi. bertujuan untuk memperluas dampak pengabdian, sehingga dapat memberikan manfaat yang lebih luas bagi dunia pendidikan dan masyarakat. Dengan demikian, pengabdian ini diharapkan dapat menjadi referensi dalam pengembangan metode pembelajaran berbasis teknologi serta membantu meningkatkan wawasan teknologi siswa agar lebih siap menghadapi tantangan digital di masa depan. Kata kunci: Hardware Komputer; Software Komputer; WawasanTeknologi; Siswa